Revitalisation of the Open and Distance Learning (ODL) Programme for Rural Dwellers’ Empowerment - Chukwunka, Clement A. C.; Onwuchekwa, Edeama O. Onwuchekwa (West African Journal of Open and Flexible Learning, 2013)
This study examined the term ’empowerment’ and the relationship between the concepts of empowerment and the quality of life in the Obohia-Ndoki community. The paper examined the need for the empowerment of Obohia-Ndoki community through the Open and Distance Learning which is a vital and indispensable instrument for the survival of the rural community. Furthermore, the Open and Distance Learning mode will invigorate the life of the community, especially among the young women who are traditional weavers. During the research process, it was observed that the activities of this traditional occupation had deprived the Obohia-Ndoki community of the pursuit of their formal education. The study concludes by asserting that the establishment of the ODL in this community will create a rejuvenation of all aspects of their life, especially their academic and social life. This empowerment will enable them to tackle the intrigues and be updated with mechanised system of the modem textile knitting and weaving. That is, it will reduce the use of the manual method of knitting garments to the more advanced method of using machines for garment fabrication. 120 respondents were randomly selected across the Obohia community and research questionnaires were administered to explore information. The hypotheses were tested using chi-square statistics at 0.10 level of significance and appropriate degrees of freedom. Results indicate ignorance, lack of economic optimum, poverty, and lack of competition as the main sustainer of the problems of the research.